Development and validation of the Lao Clinical Nurse Competency Scale - Tamura, Toyomitsu; Phanpaseuth, Souksavanh; Sisoulath, Anousone; Inthaphanith, Phengdy; Kikuchi, Shikino; Koto-Shimada, Kyoko; Fujiwara, Kazumi; Matsuda, Nobuko (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The Ministry of Health in the Lao People’s Democratic Republic (Laos) has developed a national nursing competency framework comprising five domains and 43 items, aligned with the Association of Southeast Asian Nations (ASEAN) core competencies. However, nurses’ actual competencies in Laos have not been systematically evaluated. Objective: This study aimed to develop and validate a measurement scale to assess the clinical competencies of nurses working in healthcare facilities and clinical settings in Laos. Methods: A self-administered questionnaire was created based on the National Competency for Licensed Nurses in Laos (NCLN) and distributed to 359 nurses in Vientiane Capital and Champasak Province in October 2022. Responses from 355 nurses were analyzed. Construct validity was examined using exploratory factor analysis (EFA). Structural equation modeling (SEM) was then performed solely to evaluate the goodness of fit of the proposed model, rather than to confirm the factor structure. Content validity was verified by expert review, and reliability was assessed using the Spearman–Brown coefficient, Cronbach’s alpha, and McDonald’s omega (ω). Results: The EFA identified five factors, comprising 26 items, which explained 73.2% of the variance. The SEM showed an acceptable model fit: X²(289) = 698.2, p <0.001; GFI = 0.86; AGFI = 0.83; CFI = 0.94; RMSEA = 0.066. Expert review confirmed the content validity. Reliability was high (Spearman–Brown = 0.934; Cronbach’s α = 0.880; McDonald’s ω = 0.971). Conclusion: The Lao Clinical Nurse Competency Scale (CAS) demonstrated satisfactory validity and reliability. SEM was used only to assess the model’s goodness of fit, and future studies should conduct confirmatory factor analysis (CFA) using independent samples to verify construct validity.